TBMT-01. HYPERPOLARIZED δ-[1-13C]GLUCONOLACTONE MONITORS TERT-INDUCED ELEVATION IN PENTOSE PHOSPHATE PATHWAY FLUX IN BRAIN TUMORS IN VIVO. (25th March 2021) - Batsios, Georgios; Viswanath, Pavithra; Taglang, Celine; Flavell, Robert; Costello, Joseph; Pieper, Russell O; Larson, Peder; Ronen, Sabrina
Abstract: Telomerase reverse transcriptase (TERT) expression is essential for tumor proliferation and is an attractive therapeutic target for gliomas. TERT expression has previously been shown to enhance glucose flux via the pentose phosphate pathway (PPP) in low grade gliomas expressing TERT. Hyperpolarized δ-[1- 13 C]gluconolactone has been used to detect flux via the PPP by monitoring its conversion to 6-phospho-[1- 13 C]gluconate (6PG) in isolated perfused liver. The goal of our study was to evaluate whether hyperpolarized δ-[1- 13 C]gluconolactone can be used to monitor elevated PPP flux induced by TERT expression in low grade gliomas, thereby providing a non-invasive method of assessing TERT expression in vivo . Immortalized normal human astrocytes without (NHApre) and with TERT expression (NHApost) were used in cell bioreactor experiments. In vivo experiment with rats bearing orthotopic NHApost or patient-derived low-grade oligodendroglioma (SF10417) tumors were contacted. Dynamic 13 C MR spectra were acquired at 14T (cells) or 3T (rats) following injection of hyperpolarized δ-[1- 13 C]gluconolactone. NHApost cells showed significantly higher flux through the PPP compared to NHApre. This finding was in agreement with previous results indicating that TERT expression elevates PPP flux. In all rats δ-[1- 13 C]gluconolactone and 6PG were observed indicating that δ-[1- 13 C]gluconolactone crosses the blood-brain barrier and is rapidly metabolized. Furthermore, both models presented homogeneous distribution of δ-[1- 13 C]gluconolactone in the brain and higher ratio of 6PG-to-δ-[1- 13 C]gluconolactone in the tumor area. In summary we show in vivo that hyperpolarized δ-[1- 13 C]gluconolactone metabolism to 6-phospho-[1- 13 C]gluconate is significantly higher in tumor compared to contralateral normal brain in TERT-expressing genetically-engineered and patient-derived low-grade oligodendrogliomas. Due to its fundamental role in tumor proliferation, TERT is both a tumor biomarker and a therapeutic target. Monitoring HP δ-[1- 13 C]gluconolactone metabolism, therefore, has the potential to inform on tumor burden and response to therapy in the clinic.